Stretching Exercises Can Improve Elderly Independence in Self-Care as a Preventive Measure Against Osteoarthritis - Ikrima Rahmasari; Kresna Agung Yudhianto; Hani Risnawati (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2026)
Older adults represent the final stage of human development across the life cycle. In older adults, the musculoskeletal system undergoes several changes, including changes in connective tissues (collagen and elastin), decreased cartilage function, reduced bone density, changes in muscle structure, and decreased joint elasticity. Loss of cartilage flexibility, bone hypertrophy, and thickening of the joint capsule can trigger various joint disorders. One of the most common musculoskeletal disorders found in older adults is osteoarthritis. The management of osteoarthritis is an ongoing treatment process that requires the involvement of nurses, including the implementation of stretching exercises. A stretching exercise is an activity that involves stretching the muscles to improve muscle flexibility and increase the range of motion of the joints. The purpose of this community service activity was to provide education on the topic of understanding osteoarthritis and to teach stretching exercises to older adults as an effort to promote a healthy elderly population and prevent osteoarthritis. The method used involves systematic stages and steps, including the solution implementation stage, which consists of socialization and initial data collection, and the implementation of community service. In this stage, the service team provides training on stretching exercises using a Standard Operating Procedure (SOP) that has been registered for Intellectual Property Rights (IPR). The second stage involves engaging partners in the activities, and the final stage evaluates the implementation and sustainability of the activities The community service activity was conducted in Cemani Village, RT 03/RW 10, Surakarta, with the active participation of 38 local residents. The results of the activity showed an improvement in participants’ knowledge, as demonstrated by a significant increase in the pre-test and post-test scores. Before the educational session, the majority of participants had a moderate level of knowledge (37%). Following the post-test, the majority of participants demonstrated a good level of knowledge (84%). Meanwhile, participants’ understanding of stretching exercises was evaluated based on their ability to perform the exercises independently after receiving the training.